2021
DOI: 10.1101/2021.07.12.452058
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The genomic basis of copper tolerance inDrosophilais shaped by a complex interplay of regulatory and environmental factors

Abstract: Increases in industrialisation and anthropogenic activity have resulted in an increase in pollutants released into the environment. Of these pollutants, heavy metals such as copper are particularly concerning due to their bio-accumulative nature. Due to its highly heterogeneous distribution and its dual nature as both an essential micronutrient and toxic element, the genetic basis of copper tolerance is likely shaped by a complex interplay of physiological and environmental factors. Drosophila melanogaster, a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 142 publications
0
3
0
Order By: Relevance
“…In a third dataset, we analyzed the response to infection at 19 different timepoints from 1 to 120 h after injection of Escherichia coli -derived crude lipopolysaccharide ( Schlamp et al 2021 ). Other datasets include exposure to one of 2 different viral infections, copper, starvation, radiation, and cocaine ( Palmer et al 2018 ; Prasad and Hens 2018 ; Harsh et al 2020 ; Baker et al 2021 ; de Oliveira et al 2021 ; Green et al 2021 ). A full list of accession numbers is provided in Supplementary File 1 .…”
Section: Methodsmentioning
confidence: 99%
“…In a third dataset, we analyzed the response to infection at 19 different timepoints from 1 to 120 h after injection of Escherichia coli -derived crude lipopolysaccharide ( Schlamp et al 2021 ). Other datasets include exposure to one of 2 different viral infections, copper, starvation, radiation, and cocaine ( Palmer et al 2018 ; Prasad and Hens 2018 ; Harsh et al 2020 ; Baker et al 2021 ; de Oliveira et al 2021 ; Green et al 2021 ). A full list of accession numbers is provided in Supplementary File 1 .…”
Section: Methodsmentioning
confidence: 99%
“…Note that the current version of DrosOmics provides gene annotations that were transferred to each genome from the reference release 6 of D. melanogaster (Larkin et al, 2021). Functional -omics data for 26 genomes were retrieved from previous research (Everett et al, 2020;Salces-Ortiz et al, 2020;Green et al, 2021;Horváth et al, 2022; Table 2 and Table S1) or are reported here for the first time (Supplemental Material, Table S1). Genome and functional annotations can be graphically displayed along the chromosome arms for multiple genomes simultaneously (Figure 1 and Table 2).…”
Section: Genome Browser Implementationmentioning
confidence: 99%
“…Note that the current version of DrosOmics provides gene annotations that were transferred to each genome from the reference release 6 of D. melanogaster. Functional -omics data for 26 genomes were retrieved from previous research(Everett et al 2020;Salces-Ortiz et al 2020;Green et al 2022;Horváth et al 2022; Table2 and Table…”
mentioning
confidence: 99%